2005
DOI: 10.1111/j.1440-1843.2005.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroid for persistent cough following upper respiratory tract infection

Abstract: Inhaled corticosteroid is ineffective in treating persistent post-URTI cough in previously healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Gillissen et al (2007) reported significantly faster and greater decline in cough frequency with extra-fine HFA-BDP compared with placebo in patients with cough lasting more than 3 days but less than 2 weeks. However, Pornsuriyasak et al (2005) found no effect of inhaled budesonide (400 mg twice a day) given for 4 weeks in patients with cough lasting more than 3 weeks after a URTI.…”
Section: Glucocorticosteroidsmentioning
confidence: 86%
“…Gillissen et al (2007) reported significantly faster and greater decline in cough frequency with extra-fine HFA-BDP compared with placebo in patients with cough lasting more than 3 days but less than 2 weeks. However, Pornsuriyasak et al (2005) found no effect of inhaled budesonide (400 mg twice a day) given for 4 weeks in patients with cough lasting more than 3 weeks after a URTI.…”
Section: Glucocorticosteroidsmentioning
confidence: 86%
“…Six RCTs were eligible (Table 1). [26][27][28][29][30][31] The studies were typically small, including between 30 and 276 patients (median 96, interquartile range [IQR] 76-170), and were…”
Section: Results Of the Searchmentioning
confidence: 99%
“…conducted between 2000 and 2012 in the UK, 26 Italy, 27 Netherlands, 30 Thailand, 31 Iran, 29 or multicentrically (that is, Europe, South America, and Africa). 28 They explored effects of orally administered montelukast, 26 inhaled salbutamol plus ipratropium bromide, 27 oral gelatine, 29 inhaled fluticasone propionate, 30 and inhaled budesonide 31 (Table 1). One study had three study arms investigating an orally active selective nociception opioid 1 (NOP1) receptor agonist and oral codeine.…”
Section: How This Fits Inmentioning
confidence: 99%
See 1 more Smart Citation
“…47 In another study, budesonide taken for four weeks did not reduce cough scores compared with placebo in patients coughing for three weeks or longer after an upper respiratory tract infection. 48 Two other studies evaluated the effect of inhaled beclomethasone dipropionate on cough score in patients with post-infectious acute cough (less than three weeks' duration). 49 50 In one of the studies treatment with inhaled steroid resulted in a greater reduction of cough frequency than placebo, but in the other study there was no benefit.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%